Agrochemicals influencing nitrogenase, biomass of N2-fixing cyanobacteria and yield of rice in wetland cultivation. (January 2017) - Dash, Nalinaxya Prasad; Kumar, Ajay; Kaushik, Manish Singh; Abraham, Gerard; Singh, Pawan Kumar
Abstract: Cyanobacteria maintain soil fertility by performing N2 -fixation and act as a key biocatalyst in nitrogen cycle. Chemical N-fertilizers and pesticides as agrochemicals are intensively being used in rice farming to boost rice production, this work deals with the first hand information on their influence on native N2 -fixing cyanobacteria, which play an important role in maintaining soil health. A field study was conducted for three consecutive seasons in water logged rice field to observe the influence of agrochemicals, urea, benthiocarb and carbofuran in isolation and in combinations on biomass, acetylene reduction activity (ARA) and N-yield of native cyanobacteria as well as, on growth and yield of rice. The ARA and N-yield followed almost same trend. It is discernible that both urea and benthiocarb had deleterious effects whereas, carbofuran was promoting effects on cyanobacterial growth, ARA and N-yield. The combination of all the three above agrochemicals was found inhibitory, but inhibition was comparatively less than that of urea or benthiocarb in isolation or urea plus benthiocarb treatments. It is concluded that the combination of agrochemicals was toxic, in comparison to the control, but was better than application of urea N or benthiocarb alone or with their combinations. It was recorded that along with rice straw and gain yields, panicle numbers were the maximum at the combination with treatments of benthiocarb+carbofuran. Adverse effects of used agrochemicals on cyanobacteria in wetland rice cultivation could be avoided by a prudent use of chemical N-fertilizers and pesticide(s) in combination. Highlights: Diazotrophic cyanobacteria contribute significantly to N economy in rice ecosystem. Field study on the impact of agrochemicals on cyanobacteria was carried out. Urea and benthiocarb were deleterious to cyanobacterial growth and nitrogenase activity. Carbofuran individually was promotary but agrochemical combinations were inhibitory. Conclusively urea and benthiocarb were toxic but carbofuran promoted cyanobacteria.